Food policy indicators: Tracking change - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
This section provides updates on data generated by IFPRI research and illustrations of key trends. Indicators include investments in agricultural research, public spending on agriculture, capacity for food policy research, agricultural total factor productivity, and a hunger index at the country level, as well as projections for agricultural production, food consumption, and risk of hunger to 2030 and 2050.